2019
DOI: 10.1101/581280
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stanford Accelerated Intelligent Neuromodulation Therapy for Treatment-Resistant Depression (SAINT-TRD)

Abstract: Background: Current treatments for depression are limited by suboptimal efficacy, delayed response, and frequent side effects. Intermittent theta-burst stimulation (iTBS) is a non-invasive brain stimulation treatment which is FDA-approved for treatment-resistant depression. Recent studies suggest several improvements could be made to iTBS by 1) precision targeting of the left dorsolateral prefrontal cortex (L-DLPFC) to subgenual anterior cingulate cortex (sgACC) circuit, 2) treating with multiple sessions per … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 108 publications
0
15
0
Order By: Relevance
“…Prior studies have reported significant reductions in FC between sgACC and 1 to 2 nodes of DMN (24, 37, 64-66); whereas, we observed significant reduction in FC in nearly all DMN nodes. Bearing in mind that SAINT induced remission in 90% of participants in 1-5 days (19), this question deserves careful consideration in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior studies have reported significant reductions in FC between sgACC and 1 to 2 nodes of DMN (24, 37, 64-66); whereas, we observed significant reduction in FC in nearly all DMN nodes. Bearing in mind that SAINT induced remission in 90% of participants in 1-5 days (19), this question deserves careful consideration in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that individualized targeting and enhanced stimulation techniques could improve outcomes (20), and we developed Stanford Accelerated Intelligent Neuromodulation Therapy (SAINT). In our initial open-label trial of SAINT in patients with severe, treatment-resistant depression, we observed a strikingly high remission rate of 90% with a mean of ~3 days of treatment to produce remision (19). Thus, FC changes that occur with SAINT may reflect generalized network-level changes associated with remission from depression.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations